Perlindungan Hak Anak dalam Kasus Korban Kekerasan Sosial: Perlindungan Hak Anak - Nur Arifah; Muhtar Said (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Children are legal subjects who are still not legally capable, so parents or guardians must be obliged to look after and guide the child because the parents or guardians already have legal capacity. As stated in the Declaration of the Rights of the Child or known as the Geneva Declaration on the rights of the child that the child because of his physical and mental immaturity requires special experience and care including proper legal protection both before and after his birth. Child protection is an activity to ensure and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with the dignity of humanity, and receive protection from violence and discrimination.